Treatment of genital mycoplasma in colonized pregnant women in late pregnancy is associated with a lower rate of premature labour and neonatal complications. (29th July 2014) - Vouga, M.; Greub, G.; Prod'hom, G.; Durussel, C.; Roth‐Kleiner, M.; Vasilevsky, S.; Baud, D.; Paul, M.
Abstract Mycoplasma hominis and Ureaplasma spp. may colonize the human genital tract and have been associated with adverse pregnancy outcomes such as preterm labour and preterm premature rupture of membranes. However, as these bacteria can reside in the normal vaginal flora, there are controversies regarding their true role during pregnancy and so the need to treat these organisms. We therefore conducted a retrospective analysis to evaluate the treatment of genital mycoplasma in 5377 pregnant patients showing symptoms of potential obstetric complications at 25–37 weeks of gestation. Women presenting with symptoms were routinely screened by culture for the presence of these bacteria and treated with clindamycin when positive. Compared with uninfected untreated patients, women treated for genital mycoplasma demonstrated lower rates of premature labour. Indeed preterm birth rates were, respectively, 40.9% and 37.7% in women colonized with Ureaplasma spp. and M. hominis, compared with 44.1% in uncolonized women (Ureaplasma spp., p 0.024; M. hominis, p 0.001). Moreover, a reduction of neonatal complications rates was observed, with 10.9% of newborns developing respiratory diseases in case of Ureaplasma spp. colonization and 5.9% in the presence of M. hominis, compared with 12.8% in the absence of those bacteria (Ureaplasma spp., p 0.050; M. hominis, p <0.001). Microbiological screening of Ureaplasma spp. and/or M. hominis and pre‐emptive antibiotic therapy of symptomatic pregnant women in late pregnancy might represent a beneficial strategy to reduce premature labour and neonatal complications.